TRAUMA OF GENDER: A FEMINISTIC STUDY OF SHASHI DESHPANDE’S THAT LONG SILENCE - Dr. Amrita Tyagi (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2013)
In this research paper, I am set to explore the saturation of women in India through the character Jaya in that long silence. This is the story of the journey of a girl Jaya, from her childhood to her adulthood who faced a lot of suppression and her problems continued from her being a girl to her married life with Mohan. She was mechanized to keep quiet all her life till the very end. In the end of the story, she broke her ‘that long silence’ to stand against her husband Mohan for his malpractices in the business and ends up looking at her whole life with a new perspective. Before I start to analyze the text, to support my question, I would like to throw some light on the current position of women in India and the movements that initiated the feminist movement in India. The ‘women movement’ in the year 1960 is known as the direct source of The feminist literary theory, but then it was not the start of feminism, it did work as the renewal of a very old tradition of diagnosing the problems of women in the society. Feminism in general means that the female gender having equal rights and opportunities in comparison to men in the society. In India, what I observe is that the honor and reputation of the whole family depends on the character of the female. Here, rather the honor lies between the legs of a woman. Not only this, to maintain the honor of the family, women are judged for everything they think, do or act. Every time they are under a scanner, and they are always meant to feel that, they are women in comparison to their male counterpart. This very feeling of being watched and judged creates a sense of pressure on them, and they always feel inferior of being a woman.